A triazine imidazoline latent self-crosslinking hygrothermal sizing agent for carbon fibers and its preparation method
Patent Information
- Application Number
- CN202611068952.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-27
AI Technical Summary
本发明旨在解决传统碳纤维上浆剂亲水渗水、交联密度低、湿热界面易失效的技术难题,提供一种三嗪基咪唑啉潜伏自交联耐湿热碳纤维上浆剂及其制备方法,通过分步定向化学反应构筑分子结构,实现上浆剂耐湿热、高界面结合、长储存稳定、优异工艺性的多重性能协同提升
[0017]1、分子结构可控,耐湿热性能优良;
Smart Images

Figure CN122980219A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of interface modification materials for carbon fiber composites, specifically relating to a triazine imidazoline latent self-crosslinking humid heat-resistant carbon fiber sizing agent and its synthesis and preparation method. It is applicable to various types of domestically produced carbon fibers, including T700, T800, T1000, T1100, T700 large tow, and T700 large diameter large tow, and is compatible with various high-performance resin systems such as epoxy, bismaleimide, cyanate, and polyimide resins. It can be applied to the preparation of load-bearing components of carbon fiber composites in aircraft, high-end equipment, ships, and other applications that are subjected to long-term high temperature and humidity, alternating temperature changes, and coupled water vapor erosion conditions. Background Technology
[0002] Carbon fiber reinforced composites, with their excellent properties such as lightweight, high strength, high modulus, fatigue resistance, and corrosion resistance, have become the core structural material for lightweighting in the aerospace field. Throughout the entire service life of aerospace equipment, it faces complex operating conditions such as high humidity in coastal environments, alternating temperature and humidity at high altitudes, rain condensation, and coupled erosion from damp heat and alternating loads. The interface between the fiber and the resin, as the core structure for load transfer and environmental barrier, directly determines the mechanical properties and long-term service life of the composite material due to its damp heat stability.
[0003] Currently, commercially available epoxy sizing agents for carbon fiber have two major inherent defects, which are the root causes of the significant degradation of interfacial properties after hygrothermal aging of composites: First, traditional water-based sizing agents rely on emulsifiers containing hydrophilic segments and terminal hydrophilic hydroxyl groups to achieve water dispersion. In a hygrothermal environment, a large number of hydrophilic groups form continuous water molecule diffusion channels, allowing moisture to continuously penetrate the fiber-resin interface region. Second, traditional sizing agents are mostly low-molecular-weight epoxy systems, which easily plasticize the interfacial molecular chains after water molecules penetrate, causing interfacial debonding, delamination, and microcrack propagation, ultimately leading to interfacial failure of the composite material, deterioration of mechanical properties, and reduced fiber strength conversion rate. While two-component systems using external curing agents can improve hygrothermal resistance, they suffer from poor storage stability and uneven sizing coating. Currently, foreign companies such as Toray Industries of Japan monopolize the core technology of high-end aerospace carbon fiber sizing. While their products boast excellent overall performance, they suffer from technological blockades, high procurement costs, and limited supply. Furthermore, their products still cannot fundamentally address the shortcomings of hydrophilicity and insufficient cross-linking at the molecular level, making it difficult to meet the long-life, high-reliability service requirements of China's next-generation aerospace equipment in terms of humid heat durability. Existing domestic modified sizing technologies also have significant shortcomings. Conventional latent curing systems exhibit weak reactivity and insufficient cross-linking; nano-modification systems are prone to agglomeration and have poor process adaptability; self-assembly modification processes are cumbersome and difficult to mass-produce industrially; and most products cannot simultaneously meet the three core requirements of humid heat resistance, high interfacial bonding, and excellent processability. Additionally, there is a lack of universal sizing systems adaptable to various specifications and grades of carbon fibers, with low compatibility for high-modulus T1000 / T1100 grade carbon fibers and large-tow / large-diameter carbon fibers.
[0004] To address the aforementioned technical bottlenecks, there is an urgent need to develop a single-component carbon fiber sizing agent with controllable molecular structure and possessing self-emulsifying, self-catalytic, and latent micro-crosslinking properties. This agent would block water molecule penetration at the molecular level, increase interfacial crosslinking density, and improve fiber processing performance. Simultaneously, it should be adaptable to various types and specifications of carbon fibers to meet the stringent wet and hot service requirements of the aerospace industry. Summary of the Invention
[0005] Purpose of the invention This invention aims to solve the technical problems of traditional carbon fiber sizing agents, such as hydrophilicity and water seepage, low crosslinking density, and easy failure at the humid heat interface. It provides a triazine imidazoline latent self-crosslinking humid heat resistant carbon fiber sizing agent and its preparation method. By constructing the molecular structure through stepwise directional chemical reactions, the sizing agent achieves multiple performance improvements, including humid heat resistance, high interfacial bonding, long storage stability, and excellent processability.
[0006] Technical solution
[0007] To achieve the above objectives, this invention innovatively designs a two-step directional synthesis reaction to construct a triazine-imidazoline latent crosslinking molecular system, and combines it with a flexible-rigid integrated branched polyurethane auxiliary film-forming component to prepare a high-performance, moisture-resistant, hot-water sizing agent. The core technical solution is as follows: To achieve the above objectives, this invention innovatively designs a two-step directional synthesis reaction to precisely construct a triazine-imidazoline latent crosslinking molecular system, and combines it with a flexible-rigid integrated branched polyurethane auxiliary film-forming component to prepare a high-performance, moisture-resistant, hot-water sizing agent. This agent perfectly matches the components, proportions, and process parameters defined in the claims. The core technical solution is as follows: 1. This invention breaks through the traditional random copolymerization mode and adopts a stepwise controllable reaction to construct a functional molecular framework. First, toluene diisocyanate (TDI) is used as a chemical bridge. Taking advantage of the high reactivity of the isocyanate group, the terminal hydroxyl group of alkylphenol polyoxyethylene ether (10~120 oxyethylene chain segments) is directionally linked to one of the active hydrogens of the imidazoline monomer to achieve single-end grafting. The remaining active sites of the imidazoline molecule are retained, which not only introduces hydrophilic segments of polyoxyethylene ether to achieve self-emulsification function, but also retains the sites for subsequent crosslinking reaction. Second, the highly active epoxy group of triglycidyl isocyanate (TGIC) is used to undergo a ring-opening addition reaction with the unreacted active hydrogen of imidazoline to introduce a hydrolysis-resistant and highly rigid triazine ring structure into the molecular backbone. Finally, a functional resin matrix with self-emulsification, self-catalysis and latent micro-crosslinking properties is obtained.
[0008] 2. A flexible-rigid integrated branched polyurethane is introduced as an auxiliary film-forming agent. This polyurethane is prepared by copolymerization of aromatic diisocyanate, polyether polyol and small molecule chain extender. The degree of branching is controlled at 0.25 to 0.40. The molecule has both flexible polyether segments and rigid aromatic hard segments, which can reduce the amount of fuzz on various carbon fibers, while improving the interfacial strength and toughness, relieving the interfacial stress concentration under load, and improving the fiber strength conversion rate.
[0009] 3. The functional resin synthesized in this invention has its own latent catalytic and crosslinking sites, eliminating the need for external amine curing agents. This completely avoids the defects of two-component systems, such as storage stratification, uneven sizing, and short pot life, and achieves long-term stable storage at room temperature.
[0010] Detailed preparation steps: S1. Preparation of single-ended modified imidazoline intermediate: Octylphenol polyoxyethylene ether and 2-alkyl imidazoline were dried at 80℃ for 4h to completely remove trace amounts of moisture from the system. They were then added to a dry reaction vessel at a molar ratio of 1:1. The temperature was raised to 50-55℃, and toluene diisocyanate (the overall molar ratio of the three components was 1:1:1) was slowly added dropwise under nitrogen protection. After the addition was completed, the mixture was stirred at a constant temperature for 4h. The two monomers were directionally bridged using the bifunctional characteristics of TDI, consuming only a single active hydrogen atom of imidazoline, thus obtaining a single-ended modified imidazoline intermediate that retains a single active site.
[0011] S2. Synthesis of triazine-based latent resin: The single-end modified imidazoline intermediate prepared in step S1 was heated to 100°C, and solid triglycidyl isocyanurate was added at a molar ratio of 1:1 to TGIC. The reaction was maintained at this temperature for 3 hours. The reaction was carried out by nucleophilic ring-opening addition reaction between the single epoxy group of TGIC and the remaining secondary amine of imidazoline, thus preparing a triazine-based imidazoline self-emulsifying and self-catalytic latent resin containing a rigid, humid heat-resistant triazine backbone and latent crosslinking active sites.
[0012] S3. Preparation of triazine-based epoxy emulsion: The synthesized triazine-based latent resin was placed in a homogenizing emulsification pot, heated to 65°C and stirred until completely melted. Deionized water was added in portions at a uniform rate. After the viscosity of the system increased sharply, high-speed shear homogenization was started, and reverse emulsification was carried out for 25 minutes. Deionized water was continuously added to prepare a triazine-based epoxy emulsion with a solid content of 40%. The particle size D50 of the emulsion was stably controlled in the range of 80-200 nm.
[0013] S4. Preparation of branched polyurethane emulsion: Aromatic diisocyanate and polyether polyol are mixed in proportion, prepolymerized at 75℃ for 2 hours, chain extension reaction is carried out by adding small molecule diol for 1.5 hours, triethylamine is neutralized to pH 7-8, and emulsification is carried out by adding water at high speed to prepare a flexible and rigid integrated branched polyurethane emulsion with a solid content of 30% and a branching degree of 0.32.
[0014] S5. Sizing agent compounding and emulsification: Mix triazine resin emulsion and polyurethane emulsion at a mass ratio of 5:1, and stir evenly to obtain a milky white water-based sizing agent.
[0015] Sizing application process: The prepared sizing agent is diluted with deionized water to a solid content of 1.0-1.5 wt%, and continuously impregnated with T700, T800, T1000, T1100, T700 large tow, and T700 large diameter large tow carbon fiber tows respectively. After sizing, the tows are placed in an oven at 110-135℃ for drying and curing. During the drying process, the triazine-imidazoline system triggers a controllable micro-crosslinking reaction, forming a dense, uniform, and moisture-resistant integrated interface structure on the surface of carbon fibers of different specifications.
[0016] Beneficial effects
[0017] 1. Controllable molecular structure and excellent resistance to damp heat; 2. Excellent latent self-crosslinking properties and good storage stability: It can achieve low-temperature latency and high-temperature controllable micro-crosslinking, overcoming the shortcomings of weak activity and low degree of crosslinking in traditional latent systems. This product is a single-component system, requiring no external curing agent, and can be stored for a long time without stratification or agglomeration. 3. It has wide process adaptability, is green and environmentally friendly, and can meet the uniform sizing requirements of T-series conventional carbon fiber, large tow and large diameter carbon fiber, and is suitable for industrial continuous production processes.
[0018] 4. The synergistic effect of flexible and rigid materials enhances the overall mechanical properties. The use of a flexible-rigid integrated branched polyurethane film effectively improves the wear resistance of carbon fiber surfaces, reduces fuzzy defects, optimizes interfacial stress transfer, and alleviates stress concentration. This also improves the strength conversion rate and interfacial bonding performance of carbon fibers. Attached Figure Description
[0019] Figure 1 A schematic diagram of the two-step synthetic reaction mechanism of TDI bridging and TGIC ring-opening addition in this invention; Figure 2 Comparison of interlaminar shear strength before and after humid heat in Example 2 and Comparative Example 2; Specific Implementation
[0020] Example 1 (Compatible with 12K domestic T700 grade carbon fiber) This embodiment prepares a moisture- and heat-resistant latent self-crosslinking sizing agent adapted to T700 conventional carbon fiber. The system composition is 12% triazine imidazoline latent resin, 3% flexible-rigid integrated branched polyurethane with a branching degree of 0.32, and the remaining component is deionized water. During the synthesis process, octylphenol polyoxyethylene ether with 60 ethylene oxide segments, toluene diisocyanate, and 2-alkyl imidazoline were selected and reacted strictly according to a 1:1:1 molar ratio to prepare a single-end modified imidazoline intermediate. The intermediate was then reacted with triglycidyl isocyanate (TGIC) at a 1:1 molar ratio to undergo a ring-opening addition reaction, ultimately yielding the functional latent resin. The triazine resin emulsion and polyurethane emulsion were mixed uniformly at a 5:1 mass ratio and a rotation speed of 1400 r / min. Before application, the sizing agent was diluted to a solid content of 1.2 wt% and continuously impregnated with domestically produced T700 carbon fiber. The mixture was then dried and cured at 120℃ to complete the interfacial micro-crosslinking modification. Test results show that the sizing agent emulsion D50 has a particle size of 142 nm, and exhibits excellent storage stability with no delamination or agglomeration after 12 months of storage at room temperature. After sizing, the sizing amount of T700 carbon fiber is 0.82%, the tensile strength of a single filament reaches 4.90 GPa, the fiber fuzzing amount is 1.3 mg / 50m, the interlaminar shear strength of the dry composite material at room temperature is 105.2 MPa, and the interlaminar shear strength in the wet state (tested at 82℃ after boiling in water for 48 h) is 78.8 MPa, with a retention rate of 74.9%.
[0021] Example 2 (Compatible with 12K domestic T800 grade carbon fiber) This embodiment prepares a sizing agent to meet the adaptation and modification requirements of conventional T800 carbon fiber. The system mass ratio is 15% triazine imidazoline latent resin, 2.5% flexible-rigid integrated branched polyurethane with a branching degree of 0.30, and the balance is deionized water. The synthesis raw materials and basic reaction molar ratio are consistent with those in Example 1. The mass ratio of triazine resin emulsion to polyurethane emulsion is adjusted to 6:1, the solid content of the sizing working liquid is set to 1.3wt%, and the drying and curing temperature is controlled at 125℃. The prepared sizing agent emulsion has a D50 particle size of 135nm, is stable during long-term storage at room temperature, and does not have any stratification or precipitation problems. After sizing, the T800 carbon fiber sizing amount was 0.87%, the single filament tensile strength reached 5.87 GPa, the fiber fuzzing amount was 0.9 mg / 50m, the room temperature dry state composite interlaminar shear strength was 115.3 MPa, and the wet state (tested at 82℃ after boiling in water for 48 h) interlaminar shear strength was 90.2 MPa, with a retention rate of 78.2%. (See attached figure) Figure 2 .
[0022] Example 3 (Compatible with 12K domestic T1000 carbon fiber) This embodiment is adapted for the interface modification of T1000 high-modulus carbon fiber. The sizing agent system consists of 18% triazine imidazoline latent resin, 2.0% branched polyurethane with a branching degree of 0.35, and 80% deionized water. The synthesis raw material system was optimized, using dodecyl polyoxyethylene ether with 80 ethylene oxide segments and oleo-aminoethyl imidazoline as core monomers. The molar ratio of each reaction step strictly followed the standard of ether, TDI, imidazoline 1:1:1, and the ratio of modification intermediate to TGIC 1:1. The mass ratio of resin emulsion to polyurethane emulsion was 7:1. The solid content of the sizing working liquid was adjusted to 1.4wt%, and the drying and curing temperature was increased to 130℃. The finished sizing agent emulsion has a D50 particle size of 158nm, exhibits excellent storage stability, and can effectively meet the modification requirements of high-modulus carbon fiber. The T1000 carbon fiber sizing amount is 1.01%. After sizing, the tensile strength of the T1000 carbon fiber monofilament reaches 6.37 GPa, the fiber fuzzing amount is 1.1 mg / 50m, the interlaminar shear strength of the room temperature dry composite material is 105.3 MPa, and the interlaminar shear strength in the wet state (tested at 82℃ after boiling in water for 48 h) is 78.5 MPa, with a retention rate of 74.5%.
[0023] Example 4 (Compatible with 12K domestic T1100 carbon fiber) This embodiment addresses the demanding modification requirements of T1100 ultra-high strength, high modulus carbon fiber, preparing a specialized humid heat-resistant sizing agent. The system composition is 20% triazine imidazoline latent resin, 1.8% branched polyurethane with a branching degree of 0.38, and deionized water to bring the total to 100%. The raw materials used are dinonylphenol polyoxyethylene ether with 100 ethylene oxide segments and 2-mercaptoimidazoline. The molar ratio of each reaction step was precisely controlled throughout the process. The ratio of triazine resin emulsion to polyurethane emulsion was 8:1, the solid content of the sizing working liquid was 1.5 wt%, and the drying and curing temperature was set at 135℃. Test results show that the sizing agent emulsion has a D50 particle size of 186 nm, and no particle agglomeration or stratification occurred after long-term static standing. The T1100 carbon fiber sizing amount is 1.10%. After sizing, the tensile strength of T1100 carbon fiber monofilament reaches 7.03 GPa, the fiber fuzzing amount is 1.2 mg / 50m, the interlaminar shear strength of the room temperature dry composite material is 102.3 MPa, and the interlaminar shear strength in the wet state (tested at 82℃ after boiling in water for 48 h) is 77.4 MPa, with a retention rate of 75.7%.
[0024] Example 5 (Adapted to 48K domestically produced T700 large-diameter large-tow carbon fiber) This embodiment addresses the issues of uneven sizing and poor internal wetting of domestically produced T700 large-diameter, large-tow carbon fibers. The sizing agent formulation and process are optimized. The system's mass ratio is 10% triazine imidazoline latent resin, 4.5% branched polyurethane with a branching degree of 0.28, and 85.5% deionized water. The basic synthetic raw materials are consistent with Example 1, but the mass ratio of resin emulsion to polyurethane emulsion is reduced to 3:1, the solid content of the sizing working liquid is lowered to 1.0 wt%, and the drying and curing temperature is adjusted to 130℃. The sizing agent emulsion prepared by this formulation has a D50 particle size of only 127 nm, exhibiting excellent penetration and wetting properties, which can fully fill the internal gaps of the large-tow fibers, achieving uniform sizing. After sizing, the tensile strength of T700 large-diameter large-tow carbon fiber reached 4.72 GPa, the fuzz weight was 5.8 mg / 50m, a reduction of 42%, and the surface abrasion resistance was significantly improved. The interlaminar shear strength of the room temperature dry composite material was 104.8 MPa, and the interlaminar shear strength in the wet state (tested at 82℃ after boiling in water for 48 h) was 80.2 MPa, with a retention rate of 76.5%.
[0025] Comparative Example 1: Domestic T800 carbon fiber containing traditional sizing agents.
[0026] This comparative example uses a commercially available water-based epoxy carbon fiber sizing agent to modify T800 carbon fiber. The sizing, drying, and curing process parameters are completely consistent with those in Example 2. This traditional sizing agent relies on free hydrophilic emulsifiers to achieve stability of the water dispersion system, which has inherent defects such as numerous hydrophilic groups and low crosslinking density. After sizing, the tensile strength of the carbon fiber monofilament reaches 5.82 GPa, the fiber fuzzing weight is 2.3 mg / 50m, the interlaminar shear strength of the room temperature dry composite material is 112.3 MPa, and the interlaminar shear strength in the wet state (tested at 82℃ after boiling in water for 48 h) is 76.4 MPa, with a retention rate of 68.0%. Comparative Example 2: Toray T800 carbon fiber with sizing agent: The tensile strength of carbon fiber monofilament reached 5.88 GPa, the fiber fuzzing amount was 1.8 mg / 50m, the interlaminar shear strength of the dry composite material at room temperature was 112.5 MPa, and the interlaminar shear strength in the wet state (tested at 82℃ after boiling in water for 48 h) was 79.5 MPa, with a retention rate of 70.7%.
[0027] Performance test results comparison
[0028] The wet test conditions were boiling in water at 82℃ for 48 hours followed by testing at 82℃.
Claims
1. A triazine imidazoline latent self-crosslinking, moisture-resistant carbon fiber sizing agent, characterized in that, The product comprises the following components by mass percentage: 10-40% triazine imidazoline self-emulsifying and self-catalytic latent resin, 1.5-4.5% flexible-rigid integrated branched polyurethane, and the remainder being deionized water; the triazine imidazoline self-emulsifying and self-catalytic latent resin is prepared by a stepwise reaction: first, the hydroxyl groups of imidazoline secondary amine and alkylphenol polyoxyethylene ether are bridged by toluene diisocyanate, and then the remaining active hydrogen of imidazoline is added via ring-opening reaction with the epoxy group of triglycidyl isocyanate. Its chemical structure is shown in Formula I: ,n=10~100。 2. The triazine imidazoline latent self-crosslinking humid heat-resistant carbon fiber sizing agent according to claim 1, characterized in that, The alkylphenol polyoxyethylene ether is one or more of octylphenol polyoxyethylene ether, dodecyl polyoxyethylene ether, and dinonylphenol polyoxyethylene ether, with the number of oxyethylene segments being 10 to 120, and possessing both hydrophilic self-emulsifying ability and hydrophobic and humid heat resistance.
3. The triazine imidazoline latent self-crosslinking humid heat-resistant carbon fiber sizing agent according to claim 1, characterized in that, The imidazoline is one or more combinations of 2-alkylimidazoline, 2-mercaptoimidazoline, and oleoaminoethylimidazoline. The molecular structure contains two active hydrogens. Only one active hydrogen is consumed in a single reaction, and the remaining active hydrogen is used for subsequent TGIC epoxide ring-opening addition reactions.
4. The triazine imidazoline latent self-crosslinking humid heat-resistant carbon fiber sizing agent according to claim 1, characterized in that, The triglycidyl isocyanurate (TGIC) is an epoxy monomer containing a rigid cage structure of triazine. The triazine ring has strong chemical inertness and excellent hydrolysis resistance, providing a basic moisture-resistant skeleton for sizing agents.
5. The triazine imidazoline latent self-crosslinking humid heat-resistant carbon fiber sizing agent according to claim 1, characterized in that, The flexible-rigid integrated branched polyurethane is prepared by copolymerization of aromatic diisocyanate, polyether polyol and small molecule chain extender. The molecule has both flexible buffer segments and rigid support segments, and the degree of branching is 0.25 to 0.
40.
6. The triazine imidazoline latent self-crosslinking humid heat-resistant carbon fiber sizing agent according to claim 1, characterized in that, The particle size D50 of the sizing agent emulsion is 80-200 nm.
7. A method for preparing a triazine imidazoline latent self-crosslinking, moisture-resistant carbon fiber sizing agent as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Preparation of single-terminal modified imidazoline intermediate: After drying alkylphenol polyoxyethylene ether and imidazoline at 80℃ for 4 hours, they were added to the reaction vessel at a molar ratio of 1:
1. The temperature was raised to 50-55℃, and toluene diisocyanate was slowly added dropwise under nitrogen protection. After the addition was completed, the reaction was stirred at a constant temperature for 1-6 hours. The isocyanate groups of TDI were used to connect the terminal hydroxyl groups of alkylphenol polyoxyethylene ether to a single active hydrogen of imidazoline to obtain the single-terminal modified imidazoline intermediate, retaining the remaining active hydrogen sites of imidazoline. S2. Synthesis of triazine-based latent resin: The single-end modified imidazoline intermediate prepared in step S1 is heated to 80~120℃, solid triglycidyl isocyanurate (TGIC) is added, and the reaction is maintained at the temperature for 2~4h. The triazine-based imidazoline self-emulsifying and self-catalytic latent resin is prepared by nucleophilic ring-opening addition reaction between the epoxy group of TGIC and the remaining active hydrogen of imidazoline. S3. Preparation of triazine epoxy emulsion: Triazine latent resin is heated to 50~80℃ in a homogenizing emulsification pot and stirred to melt. Deionized water is added at a uniform rate. When the viscosity of the system increases sharply, high-speed shearing or homogenization is turned on to perform reverse emulsification for 20~30 min. Deionized water is continuously added to prepare a triazine epoxy emulsion with a solid content of 30~50%. S4. Preparation of branched polyurethane emulsion: Aromatic diisocyanate and polyether polyol are mixed in proportion, prepolymerized at 70-80℃ for 2 hours, chain extended by adding small molecule diol for 1.5 hours, neutralized by triethylamine, and then emulsified with water at high speed to prepare a flexible and rigid integrated branched polyurethane emulsion with a solid content of 25-35%. S5. Sizing agent compounding and emulsification: The triazine resin emulsion prepared in step S3 and the polyurethane emulsion obtained in step S4 are compounded in a mass ratio of (3~8):1 to obtain the target waterborne carbon fiber sizing agent.
8. The preparation method according to claim 7, characterized in that, In step S1, the molar ratio of alkylphenol polyoxyethylene ether, toluene diisocyanate, and imidazoline is 1:1:1, which precisely controls the monofunctional reaction and avoids complete deactivation of the imidazoline at both sites.
9. The preparation method according to claim 7, characterized in that, In step S2, the molar ratio of the single-ended modified imidazoline intermediate to TGIC is 1:1, ensuring that only a single epoxy group of the TGIC resin undergoes ring-opening addition with the active hydrogen of the modified imidazoline.
10. The application of a sizing agent as described in any one of claims 1-6 in carbon fiber reinforced epoxy resin composites under aerospace humid and hot conditions, characterized in that, The sizing process is as follows: the sizing agent is diluted with deionized water to a solid content of 1.0-1.5 wt%, the carbon fiber bundle is continuously impregnated with the sizing agent, and dried and cured at 110-135℃. During the drying process, the triazine-imidazoline system triggers a controllable micro-crosslinking reaction to form an integrated interface structure that is resistant to moisture and heat, highly wettable, and strongly bonded.